The use of bluetooth low energy Beacon systems to estimate indirect personal exposure to household air pollution - Liao, J; McCracken, JP; Piedrahita, R; Thompson, L; Mollinedo, E; Canuz, E; De Léon, O; Díaz-Artiga, A; Johnson, M; Clark, M; Pillarisetti, A; Kearns, K; et al. (Springer Nature, 2020)
Household air pollution (HAP) generated from solid fuel combustion is a major health risk. Direct measurement of exposure to HAP is burdensome and challenging, particularly for children. In a pilot study of the Household Air Pollution Intervention Network (HAPIN) trial in rural Guatemala, we evaluated an indirect exposure assessment method that employs fixed continuous PM2.5 monitors, Bluetooth signal receivers in multiple microenvironments (kitchen, sleeping area and outdoor patio), and a wearable signal emitter to track an individual’s time within those microenvironments. Over a four-month period, we measured microenvironmental locations and reconstructed indirect PM2.5 exposures for women and children during two 24-h periods before and two periods after a liquefied petroleum gas (LPG) stove and fuel intervention delivered to 20 households cooking with woodstoves. Women wore personal PM2.5 monitors to compare direct with indirect exposure measurements. Indirect exposure measurements had high correlation with direct measurements (n = 62, Spearman ρ = 0.83, PM2.5 concentration range: 5–528 µg/m3). Indirect exposure had better agreement with direct exposure measurements (bias: −17 µg/m3) than did kitchen area measurements (bias: −89 µg/m3). Our findings demonstrate that indirect exposure reconstruction is a feasible approach to estimate personal exposure when direct assessment is not possible.